Methods of Development of Design Competents in Future Specialists - Davronova Mukhayyo Usubjanova (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
The issue of formation of technical creativity in higher educational institutions is multifaceted, it includes such an important pedagogical task as identification of effective ways of preparing students for creative activity and the appropriate selection of content, as well as the development of specific methods and means of generalizing technical creativity in the educational process the social and professional President of the Republic of Uzbekistan Sh. Mirziyoyev, October 8,2019 in the decree № PD-5847 on approval of the concept of development system of the System modernization of higher education, development of social and economic sectors based on advanced educational technologies, raising the process of training it is defined on the development OEMs. In this article highlights about methods of development of design competents in future specialists.